2021
DOI: 10.1007/s11356-021-16860-5
|View full text |Cite
|
Sign up to set email alerts
|

Current perspective on wastewater treatment using photobioreactor for Tetraselmis sp.: an emerging and foreseeable sustainable approach

Abstract: Urbanization is a revolutionary and necessary step for the development of nations. However, with development emanates its drawback i.e., generation of a huge amount of wastewater. The existence of diverse types of nutrient loads and toxic compounds in wastewater can reduce the pristine nature of the ecosystem and adversely affects human and animal health. The conventional treatment system reduces most of the chemical contaminants but their removal efficiency is low. Thus, microalgae-based biological wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 176 publications
0
11
1
2
Order By: Relevance
“…The advancement in the process such as immobilization of algal cells could improve the remediation efficiency (Goswami, Komal, et al. 2021). However, it can increase the total treatment cost.…”
Section: Challenges and Opportunities In Microalgal Based Wastewater ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The advancement in the process such as immobilization of algal cells could improve the remediation efficiency (Goswami, Komal, et al. 2021). However, it can increase the total treatment cost.…”
Section: Challenges and Opportunities In Microalgal Based Wastewater ...mentioning
confidence: 99%
“…To overcome this problem, emerging pollutant tolerant microalgae need to be screened (Rempel et al, 2021). The advancement in the process such as immobilization of algal cells could improve the remediation efficiency (Goswami, Komal, et al 2021). However, it can increase the total treatment cost.…”
Section: Challenges and Opportunities In Microalgal Based Wastewater ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tetraselmis sp. (Platymonas) is another green alga that has been identified as a source for biomass and lipid production [41] . The carbohydrate synthesis in the metabolism pathway of the Tetraselmis sp.…”
Section: Crispr-cas System As a Tool For Microbial Biofuels Productionmentioning
confidence: 99%
“…Different studies have been reported regarding the enhancement of the microalgal biomass and biomolecules, such as the optimization of physiological and environmental conditions, nutritional and physical stress, using the organic waste, modification in the cultivation vessels or systems, etc. [ 6 ]. Microalgae can be cultivated under photoautotrophic, heterotrophic and mixotrophic modes using different carbon sources.…”
Section: Introductionmentioning
confidence: 99%